ANALISIS RISIKO KESEHATAN LINGKUNGAN (ARKL) AKIBAT TRANSPORTASI KENDARAAN BERMOTOR DI KOTA SURABAYA - Ma'rufi, Isa (FSTPT Indonesia, 2015)
Environmental HealthRiskAssessment(EHRA) is an approachtocalculateorpredictthe risk tohuman health, including theidentification ofthe uncertainty factors, a searchona particularexposure, taking into accountthe inherent characteristics of concern agentandthe characteristicsof specific target. This research isa descriptive studyof riskagentsareSO2, H2S, NO2andTSP. The experiment was conductedinthe mainstreets ofSurabaya Citytolook atthe risk of environmentalhealthcaused by air pollutionmotor vehicles. Variablein this studyare the identification ofhazards, identification ofsources, analysisof exposure, dose-response analysis, riskcharacterization, environmentalhealthriskmanagement. The results ofthe studytothe levels ofrisk agentshowedthatthe highestSO2levelsinBundaranWaru Roadis 4.3mg/m3, the highestlevels ofH2Sinthe BundaranWaruis2.10,the highestlevels ofNO2inA.Yani Roadis4.1, andthe highestTSPlevelsatthe BundaranWaru is 2.46. Overall theRQvalueforeachriskagentin this study areaaccording tomore than 1(one), itmeans thatsome of the gasin the airthat comes frommotor vehiclesare veryriskyandrequirescontrol.